Modo de vida camponês e identidade indígena na Comunidade Dom Pedro II, em Barcelos, AM - Talita Pedrosa Vieira de Carvalho Benfica; Martha Benfica do Nascimento de Carvalho; Antônio Carlos Witkoski (Confins)
This paper discusses the elements of peasant production and indigenous identification in the Dom Pedro II community, in Barcelos (AM). The general objective is to analyze a particularity of the peasant universe found in Barcelos. The specific objectives are: to characterize the peasant way of life and to present the indigenous variable as one of the forms of identification of the research informants. The bibliographical survey was carried out to use the concepts: elements of peasant production, peasant way of life and indigenous identification. The primary data were collected in fieldwork, through: questionnaire application, semi-structured interview, direct observation and photographic record. The peasant represents the resistance of a non-capitalist way of life. This subject performs several work activities: cultivation (agriculture, handling of medicinal plants in the peasant property), animal extractivism (fishing and hunting) and vegetable extractivism (collection of fruits and medicinal plants). The fishing activity in Barcelos is diversified, practiced throughout the year and tied to the hydrological cycle. This activity reaches market scales that far exceed those of working with agriculture. In Barcelos, the indigenous presence is dated before the colonization, a period of great changes in its way of life and organization. Nowadays, in Barcelos, the indigenous identity encompasses relations reproduced by the interaction between the subjects and, mainly, by the common and collective shared between them. The indigenous became a form of resistance, just like the peasant. Therefore, identities are triggered, according to context, interest and situation. The multiple identities do not confuse or limit the subject; on the contrary, they reveal their totality.